Chrome spinel geochemistry of ultramafic rocks from the Elekdag metaophiolite (Northern Turkey): Implications for greenschist to mid-amphibolite facies metamorphism - Gunay, Kurtulus; Donmez, Cahit; Uysal, Ibrahim; Yildirim, Nail; Sahin, M. Bahadir; Yildirim, Esra; Lee, Insung (E Schweizerbartsche Verlagsbuchhandlung, 2016)
The Elekdag metaophiolite is located in the central part of the Pontides orogenic belt in northern Anatolia, Turkey. This metaophiolite contains blueschist units, lawsonite eclogites and completely serpentinized ultramafic rocks, and is characterized by high pressure - low temperature metamorphism. The collision and accretion processes that prevailed in the central Pontides during the Albian-Santonian interval play an important role in metamorphism of the Elekdag metaophiolite and associated units. Cr-spinels in ultramafic rocks and chromitite lenses of the Elekdag metaophiolite display multiphase alteration zoning that is revealed optically and compositionally. Chemical data from this alteration shows that Mg-Fe2+ exchange is the most important result of chromite alteration. In chromite alteration, the first stage is characterized by depletion of MgO and Al2O3 and an increase in FeOT content. Under greenschist facies conditions the primary magmatic composition is not significantly changed, whereas in the lower amphibolite facies chromite is replaced by magnetite. The last stage of chromite alteration of the Elekdag metaophiolite is represented by chromite destruction and magnetite formation with maximum FeOT, Fe2O3, FeOT/MgO, Cr#, Fe3+# and minimum Al2O3, MgO, Cr2O3, Mg#, Al# and Fe2+/Fe3+ ratios. Metamorphism of chromites indicates that the Elekdag metaophiolite possibly underwent epidote-amphibolite facies metamorphism. These processes are thought to be linked with Early Cretaceous collision/accretion processes in the central Pontides.
Keywords: Elekdag; northern Anatolia; Cr-spinels; alteration; metamorphism; ophiolite